Bilateral Comparison of Vertical Jump Landings and Step-off Landings From Equal Heights. Issue 7 (July 2018) - Harry, John R.; Freedman Silvernail, Julia; Mercer, John A.; Dufek, Janet S.
Abstract : Abstract: Harry, JR, Silvernail, JF, Mercer, JA, and Dufek, JS. Bilateral comparison of vertical jump landings and step-off landings from equal heights. J Strength Cond Res 32(7): 1937–1947, 2018—The purpose of this investigation was to examine kinetic, kinematic, and temporal parameters during vertical jump landings (VJL) and step-off landings (STL) from equal heights. Five men (25.0 ± 1.6 years; 1.7 ± 0.4 m; 79.7 ± 7.1 kg) and 5 women (20.8 ± 1.6 years; 1.6 ± 0.4 m; 68.5 ± 7.1 kg) performed 15 VJL and 15 STL. Paired-samples t -tests (α = 0.05) compared impact velocity and the times to the first (F1) and second (F2) peak vertical ground reaction force magnitudes (tF1 and tF2) and the end of impact. Two-way analyses of variance (α = 0.05) compared limb and task differences in F1, F2, hip, knee, and ankle joint angles at ground contact, F1, F2, and the end of impact, and hip, knee, and ankle joint displacements between contact and F1, F1 and F2, and F2 and the end of impact. Impact velocity was not different between STL and VJL, although STL produced a greater F1 and a more rapid tF2. Greater hip, knee, and ankle flexion/dorsiflexion occurred during STL throughout the majority of impact regardless of limb. Lesser hip, knee, and ankle joint displacements occurred during STL regardless of limb between F1 and F2, whereas greater joint displacement occurred between F2 and the end of impact. Lastly, knee joint angles at ground contact differed between limbs during STL only. Strength and conditioning professionals aiming to improve an athlete's performance during sport-specific jump landings should consider the likely impact attenuation outcomes before selecting STL or VJL in training.